TEACHING ENGLISH TO YOUNG LEARNERS IN RURAL AREAS: TEACHERS’ CHALLENGES - Nasution, Safitri Adriani; Daulay, Sholihatul Hamidah; Rahman, Benni Ichsanda (TELL - US JOURNAL, 2023)
English teachers in rural schools face many challenges. The difficulties encountered in English learning in rural schools are related to the condition of the students, the environment, and the English teacher's competence. This study aims to explore the challenge that arises in English language learning in rural schools. This study used a qualitative method design with four English teachers from four different schools as respondents. The results of this study show that there are still many obstacles encountered in teaching English to young learners in rural schools. English language learning for young learners in rural areas needs to be improved for several reasons. Including low student interest in English lessons, lack of support for English learning, such as support from parents and the surrounding environment, and the quality of English teachers, who are considered low.